Economic and Social Dimensions of Uang Panai in the Bugis Tribe - Sudarman, Suhaily; Burhan, Umar; Manzilati, Asfi (Journal of International Conference Proceedings, 2023)
This study aims to determine the economic and social dimensions of Uang Panai among the Bugis tribe. The type of research used is qualitative with a phenomenological approach, namely explaining the results of research on phenomena that exist in people's lives. Data collection uses interviews with relevant informants, observation and documentation. The research results obtained are that uang panai can be seen from the economic dimensions and social dimensions. When viewed from the economic dimension, Uang Panai will be formed due to the interaction of bargaining between the two parties (man and woman), the man makes the request, party of the woman becomes the supplier, the woman becomes the item offered and Uang Panai becomes the price. The amount of Uang Panai is determined by several factors, namely the level of education, profession, the price of staples and the cost of the wedding ceremony. Meanwhile, if Uang Panai is seen from the social dimension, then it is related to people's lives that affect the amount of Uang Panai. Factors that influence the amount of Uang Panai on the social dimension are customs, nobility, social status, and the influence of the area or the surrounding community.